1988
DOI: 10.1051/rnd:19880310
|View full text |Cite
|
Sign up to set email alerts
|

The role of the pineal gland in the photoperiodic control of reproduction in different hamster species

Abstract: Introduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(65 citation statements)
references
References 54 publications
2
58
0
2
Order By: Relevance
“…The best example of such photoperiod-dependent physiological functions is the activation/inactivation of the reproductive axis, a phenomenon in which the pineal and its MEL rhythm are essential. Numerous studies have now demonstrated that the pineal gland is a neuroendocrine transducer receiving photoperiodic information from the retina and circadian SCN oscillator, and transmitting this to the reproductive system via a particular dynamic pattern of MEL secretion (see Hoffmann, 1979;Reiter, 1980;Goldman and Darrow, 1983;Bittman, 1984;Tamarkin et al, 1985;Pévet, 1988;Goldman, 2001 for reviews). However, several fundamental questions remain before the role of MEL in the regulation of seasonal function is elucidated: 1) where is the photoperiodic information encoded before its translation into the MEL rhythm?…”
Section: A Regulation Of Seasonal Rhythmsmentioning
confidence: 99%
“…The best example of such photoperiod-dependent physiological functions is the activation/inactivation of the reproductive axis, a phenomenon in which the pineal and its MEL rhythm are essential. Numerous studies have now demonstrated that the pineal gland is a neuroendocrine transducer receiving photoperiodic information from the retina and circadian SCN oscillator, and transmitting this to the reproductive system via a particular dynamic pattern of MEL secretion (see Hoffmann, 1979;Reiter, 1980;Goldman and Darrow, 1983;Bittman, 1984;Tamarkin et al, 1985;Pévet, 1988;Goldman, 2001 for reviews). However, several fundamental questions remain before the role of MEL in the regulation of seasonal function is elucidated: 1) where is the photoperiodic information encoded before its translation into the MEL rhythm?…”
Section: A Regulation Of Seasonal Rhythmsmentioning
confidence: 99%
“…In mammals, a dedicated photoneuroendocrine system (fig. 1) transduces the ambient photoperiod to control the production of the hormone melatonin [3,4,5,6,7], which in turn coordinates physiological functions, such as reproductive activity, to the photoperiod [3,4,5]. …”
Section: Seasonal Control Of Reproduction: From Photonic Energy To Spmentioning
confidence: 99%
“…Seasonal reproduction is a complex biological phenomenon, which relies on both internal and external environments. Photoperiod is a typical seasonal variation that regulates reproduction in seasonal breeders, and most seasonal breeders modulate reproductive activity by responding to the photoperiod (Pévet, 1988;Bartke and Steger, 1992;Goldman, 2001;Prendergast, 2005). Photoperiodic information can be transmitted to the reproductive system by melatonin (Simonneaux et al, 2009), which is a pineal hormone that is secreted at levels which are proportional to the night length.…”
Section: Introductionmentioning
confidence: 99%